2015
DOI: 10.1002/hipo.22532
|View full text |Cite
|
Sign up to set email alerts
|

Sweet orosensation induces Arc expression in dorsal hippocampal CA1 neurons in an Experience‐dependent manner

Abstract: There is limited knowledge regarding how the brain controls the timing of meals. Similarly, there is a large gap in our understanding of how top-down cognitive processes, such as memory influence energy intake. We hypothesize that dorsal hippocampal (dHC) neurons, which are critical for episodic memory, form a memory of a meal and inhibit meal onset during the postprandial period. In support, we showed previously that reversible inactivation of these neurons during the period following a sucrose meal accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 96 publications
4
13
0
Order By: Relevance
“…The finding that increased sucrose experience prevented the ability of sucrose ingestion to elevate dHC pSer 831 is consistent with previous findings showing that the ability of a stimulus to activate pSer 831 depends on the history of synaptic activation [74], and with our previous results showing that increased sucrose experience attenuates sucrose-induced increases in dHC Arc expression [71]. Together, the Arc and pSer 831 results suggest that repeated consumption of the same meal may decrease the mnemonic demands associated with that meal and/or that the role of the hippocampus in remembering the last meal may diminish when the energy source is not novel and consumed habitually.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that increased sucrose experience prevented the ability of sucrose ingestion to elevate dHC pSer 831 is consistent with previous findings showing that the ability of a stimulus to activate pSer 831 depends on the history of synaptic activation [74], and with our previous results showing that increased sucrose experience attenuates sucrose-induced increases in dHC Arc expression [71]. Together, the Arc and pSer 831 results suggest that repeated consumption of the same meal may decrease the mnemonic demands associated with that meal and/or that the role of the hippocampus in remembering the last meal may diminish when the energy source is not novel and consumed habitually.…”
Section: Discussionsupporting
confidence: 92%
“…The present finding that sucrose ingestion increased dHC GluA1 pSer 831 is consistent with our previous results showing that sucrose ingestion elevates dHC expression of the plasticity-related immediate early gene activity-regulated cytoskeleton-associated protein ( Arc ) [71]. Of note, both GluA1 pSer 831 and Arc expression are dependent on activation of the glutamate NMDA receptor [72,73] and are critical for synaptic plasticity [74,75].…”
Section: Discussionsupporting
confidence: 92%
“…One question that arises is whether they do so through similar or different underlying mechanisms. Our finding that sucrose ingestion increases Arc expression in both dHC (Henderson et al, ) and vHC (present findings) neurons is consistent with the possibility that both dHC and vHC neurons regulate intake through a process that involves memory. It is possible that dHC neurons encode the “what, where, and when” components of a recently eaten meal (Eichenbaum, ; Shapiro et al, ); whereas, vHC neurons encode the affective/emotional aspects (Fanselow and Dong, ; Strange et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Evidence from intact humans provides indirect support for the involvement of memory dysfunction, however, by showing that HC‐dependent memory does indeed influence future intake (Robinson et al, ). Moreover, satiety cues are likely needed to form a memory of a meal, which is supported by findings showing that postprandial signals such as leptin increase synaptic plasticity in HC (Shanley et al, ; Harvey et al, ), and by our findings showing that sucrose intake increases dHC (Henderson et al, ) and vHC Arc expression (present findings). Additional data are needed to resolve whether dHC and vHC inactivation‐induced increases in intake are due to impaired ability to detect interoceptive cues, a deficit in the interpretation or use of those cues, and/or impaired consolidation of the memory of the meal.…”
Section: Discussionsupporting
confidence: 89%
“…Parent and colleagues (2013) have elegantly modeled this phenomenon in rodent models, demonstrating that reversible inactivation of hippocampal neurons immediately following a scheduled, anticipated sucrose meal reduces meal initiation latency and increases the size of the subsequent meal [26]. This group more recently demonstrated that orosensory stimulation through either intake of sucrose or non-caloric saccharin robustly increases hippocampal synpatic plasticity in an experience-dependent manner [27]. Together, these results suggest that 1) hippocampal neural processing can regulate the consolidation of food-related declarative memories, and 2) disrupted hippocampal processing can potentially lead to excessive eating.…”
Section: Mnemonic Control Of Food Intakementioning
confidence: 99%